Programa de assistência ao parto e recém-nascido do município de Botucatu/SP: resultados de 1999 - Cardoso, Adilson Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
Objective – To evaluate the effectiveness of the hierarchyzation process in the Delivery and Newborn Assistance Program in Botucatu City. Patients and methods – A prospective and comparative study carried out from January 1 to December 31, 1999. It was compared the results of two delivery assistance services in convenant with SUS and differenciated at the level of secondary (HR-ABHS) and tertiary (HC-FMB/Unesp) attention. Maternal age, parity, consultations number, place of prenatal, type of delivery, indications for Caesarean, gestational age, weight at birth, Apgar indexes, cause of hospitalar maternal mortality and precocious neonatal mortality were related. For statistical analysis, it was used the ?2 and Goodman tests, with significance level at 5% (p

Objetivo – Avaliar a efetividade do processo de hierarquização no Programa de Assistência ao Parto e Recém-nascido do Município de Botucatu (SP). Pacientes e métodos – Estudo prospectivo e comparativo realizado no período de 01 de janeiro a 31 de dezembro de 1999. Foram comparados os resultados de dois serviços de assistência ao parto, conveniados ao SUS e diferenciados em nível de atenção secundária (HR-ABHS) e terciária (HC-FMB/Unesp). Foram relacionados idade materna, paridade, número de consultas e local de realização do pré-natal, tipo de parto, indicações de cesárea, idade gestacional e peso ao nascimento, índices de Apgar, razão de mortalidade materna hospitalar e mortalidade neonatal precoce. Para a análise estatística foram utilizados os testes de ?2 e de Goodman, com nível de significância de 5% (p
Delivery and newborn assistance program in Botucatu city, São Paulo State, Brazil – results of 1999
Keywords: Attention levels; Delivery assistance; Maternal and neonatal results; Biológicas; Saúde; Níveis de atenção; Assistência ao parto; Resultados maternos e neonatais